Wound Repair and Regeneration - Allison Cowin (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Wounds are a largely unrecognized, spiraling epidemic that affect millions of people world-wide. They are complex and involve temporal and spatial involvement of many different cell types and tissue processes. Recent advances in our understanding of wound repair and regeneration, as well as the many novel and exciting approaches aimed at healing chronic/acute wounds and reducing scar formation, make this a pertinent time for a Special Issue aimed at overviewing this important field. The goal of this book is to provide a summary of the field, describe its impact, as well as introduce the recent advances in understanding the mechanisms that underpin wound healing and scar formation. The articles include in this book highlight new developments in therapeutic approaches for wound repair including the use of nanomedicine and biomaterials to deliver cells and/or drugs to promote healing. Cellular responses that underpin angiogenesis, inflammation, proliferation and remodeling, as well as advances in cytoskeletal interactions in keratinocytes and fibroblast cell functions. Wound remodeling and scar formation including the roles of growth factors, cytokines and stem cells are included.